Cardiotoxicity after autologous hematopoietic stem cell transplantation (AHSCT): longitudinal and observational study - Elias Hallack Neto, Abrahão (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
Objectives: To assess incidence and extent of early cardiotoxicity after autologous hematopoietic stem cell transplantation (AHSCT). Methods: Study carried out in two bone marrow transplant centers, in public and private hospital, located in interior of Minas Gerais, Brazil. All patients who underwent AHSCT at centers between March 2018 and May 2019 and October 2019 were included. Altered results were classified according to Brazilian Cardio-Oncology Guidelines. Results: Of the 36 patients evaluated, seven (21.2%) had cardiotoxicity on echocardiography, with mean left ventricular ejection fraction decreasing from 71.53 to 64.75% before and after conditioning (p = 0.00013). Clinical cardiovascular alterations were associated with advanced staging and time of more than one year between diagnosis and AHSCT (p=0.01 in both cases). Specific clinical signs of congestion were correlated with radiotherapy to the mediastinum and a dose >400 mg of doxorubicin before AHSCT (p=0.02 and p=0.01, respectively). Conclusions: Thus, higher incidence of cardiac injury was observed after AHSCT, which was related to type of pre-transplant therapy. This fact reflects our limitations and leads us to seek improvements in cardiovascular assessment of patients undergoing AHSCT, in order to reduce morbidity and mortality associated with myocardial injuries in these patients.